(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
There are two distinct approaches to modelling the term structure of interestrates. The first is essenciallly to measure the term structure using statistical techniques by appliyng interpolation or curve-fitting methods to construct yields.The second approach is based on models, known as dynamic models, which make explicit assumptions about the evolution of state variables and asset pricing models using either equilibrium or arbitrage arguments. There is no consensus on any particular methodology and the choice between alternative curve modelsis, in part, subjective. Nevertheless, the interpolation or curve-fitting methods have showed good properties and are those used nowadays by the vast majority of central banks.The objective of this article is to present the principal methodologies that have been proposed for the TSIR estimation. A better understanding of the different methodologies and their limitations will provide the researchers with an overview ofthe problematic of estimation of the yield curve and will enable them to choose the best model according to their objectives.